2015
DOI: 10.1038/srep15559
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Reduce Murine Atherosclerosis Development

Abstract: Mesenchymal stem cells (MSCs) have regenerative properties, but recently they were also found to have immunomodulatory capacities. We therefore investigated whether MSCs could reduce atherosclerosis, which is determined by dyslipidaemia and chronic inflammation. We adoptively transferred MSCs into low-density lipoprotein-receptor knockout mice and put these on a Western-type diet to induce atherosclerosis. Initially after treatment, we found higher levels of circulating regulatory T cells. In the long-term, ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 58 publications
10
50
0
Order By: Relevance
“…In line with previous results, Vanessa Frodermann et al also displayed that BM-MSCs were able to reduce atherosclerosis via modulating inflammatory responses and reducing dyslipidaemia in mice [43]. In this study, they fed LDLr KO mice a WTD for 8 weeks to build an atherosclerotic model.…”
Section: Bone Marrow-derived Mscs In Atherosclerosissupporting
confidence: 86%
“…In line with previous results, Vanessa Frodermann et al also displayed that BM-MSCs were able to reduce atherosclerosis via modulating inflammatory responses and reducing dyslipidaemia in mice [43]. In this study, they fed LDLr KO mice a WTD for 8 weeks to build an atherosclerotic model.…”
Section: Bone Marrow-derived Mscs In Atherosclerosissupporting
confidence: 86%
“…Although this is a different disease model, hyperlipidemia may have also influenced MSC trafficking in our chronic model, which could explain that MSC treatment did not lower atherosclerosis and emphysema development in the current study. Furthermore, a study by Frodermann et al [ 26 ] , where MSC were adoptively transferred in LDLr-/- mice, showed lowered cholesterol levels and atherosclerosis development. Whereas MSC were isolated from WT mice in that study, we used MSC isolated from E3L mice, which may be functionally different from WT MSC, however future research is necessary to determine this.…”
Section: Discussionmentioning
confidence: 99%
“…So far, MSC treatment has been evaluated in a few clinical trials in COPD and was found to be safe, although currently little effects on disease outcomes were observed [ 21 – 23 ]. Also several mouse models of atherosclerosis show that treatment with MSC reduces CVD [ 24 – 26 ]. Since current treatment of COPD patients with CVD is suboptimal, the aim of this study was to investigate the immunomodulatory properties of MSC on pulmonary and systemic inflammation, emphysema and atherosclerosis in an acute and chronic murine model of LPS-induced pulmonary inflammation using hyperlipidemic APOE*3-Leiden ( E3L ) mice, which develop diet-induced atherosclerosis [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the effect of administrating the combination therapy of kefir with GB on ACAT brain tissue expression, a down regulation in the expression of ACAT was observed [89], reported the ability of GB to inhibit the production of AÎČ plaques by lowering the levels of circulating free cholesterol and intracellular cholesterol levels leading to miss folding in APP processing and amyloidogenesis by its antioxidant, antiinflammatory, immune modulatory and antiplatelet aggregation effects as well as the ability to polarize microglia to engulf excessive cholesterol due its immune modulatory effect [90].In our previous study, we observed the ability of kefir to decrease cholesterol and lipid level by increasing the discharge of bile acids [12]. Regarding the present study, we believe that kefir has the ability to suppress ACAT which in turn decrease cholesterol ester level and intracellular cholesterol due to its oxidative scavenging, anti-inflammatory and anti-oxidant effects leading to rapid down regulation of APP neurons protein content with reducing AÎČ production in vivo and in vitro [85][86][87][88][89][90].…”
Section: Discussionmentioning
confidence: 49%
“…A relevant increase in brain tissue CBS relative expression was obtained in accordance with [74,[82][83] Where MSCs are vital progenitor cells owing the capability to differentiate into vital cells with maintaining tissue homeostasis and proliferation of neural stem cells. While a suppression in oxidative stress brain tissue level (MDA) with a simultaneous increase in (GSH) was observed following intracerebral MSCs transplantation.These obtained results are in accordance with [12], where oxidative stress markers in brain tissue were suggested to be suppressed by intracerebral transplantation of MSCs as a result of expressing antiinflammatory cytokines involved in brain tissue repair introduced by MSCs via Bcl2 activation with attenuating Bax expression preventing brain damage [12,84].An additional beneficial action of transplanting MSCs intracerebrally within LPS induced AD in rats was their ability to suppress ACAT brain tissue relative expression level, which can not only be related to the lipid engulfing macrophage polarization effect but also to its ability to suppress inflammatory cascades such as TNF-α expression and caspase-3 where they play a vital role in up regulating the brain cholesterol ACAT level [12,[85][86].…”
Section: Discussionmentioning
confidence: 99%